Experience-Based Student Entrepreneurship Education: An International Collaborative Approach - Fadhil, Rahmat; Ramadhani, Evi; Hussain, Mohd Rizal Bin; Dinaroe, Dinaroe; Rahimi, Sayyid Afdhal El; Zuhri, Sarika; Halim, Hendra; Sulaiman, Juliah Binti; Syahfitri, Widya (Jurnal Pengabdian Bakti Akademisi, 2025)
This community service activity addresses the gap between entrepreneurial theory and practical experience among university students, particularly in preparing them to become job creators. The aim of this initiative was to enhance students entrepreneurial competence through a collaborative and experience-based learning model. Conducted as an international collaboration between Universitas Syiah Kuala, Indonesia, and Politeknik Seberang Perai, Malaysia, the activity employed a Service Learning approach involving interactive sessions, group discussions, and business model design. Students were exposed to real-world entrepreneurial practices presented by experts from both institutions. The results showed a significant improvement in students understanding and ability to develop viable business ideas using the Business Model Canvas. Participants demonstrated increased confidence and motivation to pursue entrepreneurship, and the activity contributed to developing practical skills aligned with sustainable development goals. This program model presents a replicable approach for enhancing entrepreneurial education through cross-border academic collaboration and experiential learning.